Parole de mort-vivant - Ariane Bottex-Ferragne (Revue des Langues Romanes)
This article seeks to rethink the fantastic as a literary mode of the supernatural by moving beyond its traditional association with fiction and narration. Focusing instead on a corpus of moralizing and religious poetry, the analysis centers on the extensive body of medieval French poems written in the so-called Helinand’ stanza (8aabaabbbabba). Through an archive-based approach, it highlights the historical and literary connections between these poets’ ethos and figures of the “living dead”, ultimately showing that Helinandian voices may inhabit a liminal space that blurs the very boundaries between life and death.Middle Ages, supernatural, fantastic, moralizing and religious poetry, Helinand Stanza